Book Review: Grounded Theory: A practical guide (Birk & Mills, 2011) - Astrid Gynnild (Grounded Theory Review: An International Journal, 2011)
What is grounded theory and how is a grounded theory study carried out? Several recent publications have been trying to answer these questions, building on a literature list on the topic that covers more than 40 years of research and scholarship. According to the authors, this book is aimed at beginner researchers, research students and experienced researchers from a variety of disciplines who are unfamiliar with grounded theory.